PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 1 JARO KECAMATAN JARO KABUPATEN TABALONG - Hatmiah Hatmiah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The learning carried out by good Islamic religious education teachers is expected to support a better Islamic religious education learning process. This statement can be formulated as the focus of this research, which is about learning Islamic religious education at SMAN 1 Jaro, Jaro District, Tabalong Regency. The purpose of this study was to determine the learning of Islamic religious education at SMAN 1 Jaro, Jaro District, Tabalong Regency. This research is a field research. The subjects in this study were 1 Islamic religious education teacher and students at SMAN 1 Jaro, Jaro District, Tabalong Regency. The object of this research is learning Islamic religious education at SMAN 1 Jaro, Jaro District, Tabalong Regency. Data collection techniques using observation, interviews and documentation. Data processing techniques use data reduction, data display, and data verification. The analysis used is descriptive qualitative analysis. The results of this study indicate that the learning of Islamic religious education at SMAN 1 Jaro, Jaro District, Tabalong Regency is going well.